Penerapan Restoratif Justice Sebagai Upaya Mengurangi Overcapacity Lapas - Dafa Pansya Dila, M; Raisa Monica, Dona; Dewi, Erna; Raharjo, Eko; Berdian Tamza, Fristia (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
Overcapacity in correctional institutions (prisons) in Indonesia is a serious problem that affects the physical, mental and social conditions of prisoners and hinders rehabilitation and reintegration functions. This research analyzes the application of restorative justice as an effort to reduce overcapacity in prisons. Normative research methods are used to explore literature from relevant journals, books, websites and official documents. Restorative justice, which emphasizes restoration and reconciliation through dialogue between perpetrators, victims, and the community, offers alternative punishments outside prison such as mediation, community service, and community-based rehabilitation programs. The research results show that restorative justice can reduce the prisoner population, improve the quality of rehabilitation and reintegration, increase victim satisfaction, and create a safer and more humane prison environment. However, the implementation of restorative justice in Indonesia still faces various challenges, including lack of understanding, limited resources, and resistance from prisoners and victims. With more coordinated efforts and adequate support, restorative justice has great potential to bring significant positive change to the penal system in Indonesia.